Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian - Nuuru Rizky Ammalia; Supriyono Supriyono (IPM2KPE, 2022)
This study aims to determine the effect of product quality and price perceptions on Samsung Smartphone purchasing decisions. This research method is descriptive quantitative. The research population was taken from East Java